Piacenza - Los Angeles libri d'arte e poesia (1991-2008) dall'archivio di Michele Lombardelli - Lombardelli, Michele 1968-; Nicolin, Paola; Du Pasquier, Nathalie 1957-; Vangelisti, Paul 1945- (Mousse Publishing, 2024)
Published on the occasion of the eponymous exhibition curated by Paola Nicolin at XNL Piacenza, Michele Lombardelli: Piacenza – Los Angeles offers a literary bridge between these two very different cities through the art and poetry publications edited by Lombardelli between 1991 and 2008. Over the years, Lombardelli’s work has facilitated artistic encounters with some of the most brilliant personalities from Emilia, such as William Xerra, Carlo Berté, Mauro Sargiani, Emilio Villa, and Aldo Tagliaferri, as well as with great US poets and artists like Robert Crosson, John Baldessari, Martha Ronk, Dennis Phillips, and Guy Bennett. This network of exchanges and friendships forms the basis of the volume, in which Lombardelli, together with his friend, the poet Paul Vangelisti, skillfully intertwine poetry, visual arts, music, and literature
Impressum: Questo catalogo é stato pubblicato in occasione della mostra "Michele Lombardelli. Piacenza - Los Angeles. Libri d'arte e poesia (1991-2008) dall'archivio di Michele Lombardelli", 22 aprile 2023 - 18 giugno 2023, XNL Piacenza, Centro d'arte contemporanea, cinema, teatro e musica
Keywords: Lombardelli, Michele -- 1968-; Geschichte 1991-2008; Lyrik; Künstlerbuch; Herausgeber; Umkreis; Los Angeles, Calif.; Piacenza; Ausstellungskatalog -- XNL Piacenza. Centro d'arte contemporanea, cinema, teatro e musica -- 22.04.2023-18.06.2023 -- Piacenza